2006
DOI: 10.22514/sv11.102006.2
|View full text |Cite
|
Sign up to set email alerts
|

Intraabdominal hypertension and abdominal compartment syndrome in the intensive care unit

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…It is important to note that ACS may develop in any critically ill patient even though it most commonly follows abdominal trauma and damage control laparotomy [3]. Using just an abdominal physical exam alone is not an adequate method of detecting an elevated IAP.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is important to note that ACS may develop in any critically ill patient even though it most commonly follows abdominal trauma and damage control laparotomy [3]. Using just an abdominal physical exam alone is not an adequate method of detecting an elevated IAP.…”
Section: Discussionmentioning
confidence: 99%
“…ACS most often results from blunt abdominal trauma with intra-abdominal bleeding but may even be due to the compressive effect of intra-abdominal packing [3]. Other etiologies include ruptured abdominal aortic aneurysm, liver transplantation, postpartum hemorrhagic pancreatitis, bowel obstruction, abdominal growths, ascites, and secondary ACS from massive volume resuscitation [2, 4].…”
Section: Introductionmentioning
confidence: 99%
“…This development of IAH‐induced organ dysfunction and failure over time is regarded as ACS (Cheatham 2009). It has been further reported that the gastrointestinal and renal systems are usually affected first (Pavlovic and Kogler 2006; de Waele et al . 2011).…”
Section: Definitions Of Iah and Acsmentioning
confidence: 99%
“…This development of IAH-induced organ dysfunction and failure over time is regarded as ACS (Cheatham 2009). It has been further reported that the gastrointestinal and renal systems are usually affected first (Pavlovic and Kogler 2006;de Waele et al 2011). The importance of IAH in human medicine has been recently exemplified by inauguration of a World Society of the Abdominal Compartment Syndrome (WSACS) with a mission to promote research, foster education, and improve the survival of patients with IAH and/or ACS (http://www.wsacs.org).…”
Section: Definitions Of Iah and Acsmentioning
confidence: 99%